Long term, continuous exposure to panobinostat induces terminal differentiation and long term survival in the TH‐MYCN neuroblastoma mouse model. Issue 1 (10th March 2016) - Waldeck, Kelly; Cullinane, Carleen; Ardley, Kerry; Shortt, Jake; Martin, Ben; Tothill, Richard W.; Li, Jason; Johnstone, Ricky W.; McArthur, Grant A.; Hicks, Rodney J.; Wood, Paul J.
Abstract : Neuroblastoma is the most common extra‐cranial malignancy in childhood and accounts for ∼15% of childhood cancer deaths. Amplification of MYCN in neuroblastoma is associated with aggressive disease and predicts for poor prognosis. Novel therapeutic approaches are therefore essential to improving patient outcomes in this setting. The histone deacetylases are known to interact with N‐Myc and regulate numerous cellular processes via epigenetic modulation, including differentiation. In this study, we used the TH‐MYCN mouse model of neuroblastoma to investigate the antitumor activity of the pan‐HDAC inhibitor, panobinostat. In particular we sought to explore the impact of long term, continuous panobinostat exposure on the epigenetically driven differentiation process. Continuous treatment of tumor bearing TH‐MYCN transgenic mice with panobinostat for nine weeks led to a significant improvement in survival as compared with mice treated with panobinostat for a three‐week period. Panobinostat induced rapid tumor regression with no regrowth observed following a nine‐week treatment period. Initial tumor response was associated with apoptosis mediated via upregulation of BMF and BIM. The process of terminal differentiation of neuroblastoma into benign ganglioneuroma, with a characteristic increase in S100 expression and reduction of N‐Myc expression, occurred following prolonged exposure to the drug. RNA‐sequencing analysis of tumors from treated animals confirmed significant upregulation of gene pathways associated with apoptosis and differentiation. Together our data demonstrate the potential of panobinostat as a novel therapeutic strategy for high‐risk neuroblastoma patients. Abstract : What's new? Poor prognosis in neuroblastoma is strongly linked to amplification of the proto‐oncogene MYCN, the product of which, N‐myc, interacts with histone deacetylases (HDACs). Epigenetic modulation by HDACs regulates key tumor‐related cellular activities, including differentiation. This study shows that epigenetic modulation of murine neuroblastoma via HDAC inhibition promotes a terminal‐differentiation phenotype in the TH‐MYCN mouse model, resulting in a sustained survival benefit in more than 90% of treated mice. Continuous, prolonged panobinostat exposure was required to produce this effect. The findings raise questions regarding current HDAC inhibitor dosing schedules and how best to incorporate the drugs into neuroblastoma treatment protocols.